Letter from J. Manning Post - J. Manning Post:::::: (1976)
A December 10, 1976 letter from the California Carter/Mondale Inaugural Committee announces the formation of a committee to coordinate transportation and hotel accommodations for Californians attending the Presidential Inauguration. The four-day trip to Washington, D.C. would include charter flights, hotel stays, and access to several events such as a Congressional Cocktail Party, a Kennedy Center tour and luncheon, receptions, the Swearing-In Ceremony (limited availability), and the Inaugural Ball, at an estimated cost of $750–$850. The letter urges prompt responses due to limited space and provides contact information for further details.